Psychosocial Considerations on Victims of Traumatic Events: An Approach from the Experience in an Assistance Unit of the Peruvian Public Department - Alonso Manuel Paredes Paredes (Psychosocial Considerations on Victims of Traumatic Events: An Approach from the Experience in an Assistance Unit of the Peruvian Public Department, 2021)
The present study explores some important psychosocial elements in victimological assistance for people who were victims of misdemeanors and crimes. Thus, 14 situations corresponding to assisted cases at the offices of an Immediate Unit Assistance for Victims and Witnesses of Peru were selected. Situations that have been analyzed by integrating different theoretical, epistemological and methodological contributions in an eminently qualitative approach, achieving to highlight the importance of social, professional and community environment in a transdisciplinary link. The values and prejudices of the intervener who is faced to diverse situations that concomitantly require the analysis of his capabilities and limitations in order to improve the quality of his interventions and contribution to the exercise of justice are also considered.